Typical gut indigenous bacteria in ICR mice fed a soy protein-based normal or low-protein diet - Saori Nakamura; Takashi Kuda; Yuko Midorikawa; Hajime Takahashi; Bon Kimura (Current Research in Food Science, 2021)
For patients with inflammatory bowel disease, cow’s milk allergy, and lactose intolerance, soymilk is a potential alternative to cow’s milk. In this study, we aimed to identify the effects of a soy protein-based low-protein diet on the body and organ weights and the gut microbiome of six-week-old mice fed a diet containing 20% (SP) or 5% (LP) soy protein for 14 days via 16S rRNA (V4) amplicon sequencing. Body weight gain (growth) and liver, spleen, and fat tissue weight were significantly suppressed by the LP diet. Operational taxonomic unit numbers and α-diversity were lower in the LP group than in the SP group. A principal coordinate analysis revealed differences in the gut microbiome compositions of SP and LP mice. The abundances of caecal Roseburia sp., Alistipes sp., and bacteria from the family Muribaculaceae were lower in the LP group than in the SP group. In contrast, the abundance of Desulfovibrionaceae, which is positively correlated with inflammation, was higher in the LP group than in the SP group. These results differed from the effects of a milk casein-based low-protein diet (reported previously). Based on these findings, we conclude that the undesirable effects of a low-protein diet and/or protein deficiency are related to changes in the gut microbiome composition and may differ depending on the kind of proteins used.